Research in Science Education in India - Koireng, R.R. (INDIAN EDUCATIONAL REVIEW, 2020)
Realising the importance of improving the practice of teaching-learning of science in schools, science education has, in recent years, emerged as an independent field of research. The paper reviews science education research, conducted after 2000 related to the issues and concerns of teaching and learning of science in Indian schools. It includes research reports, research journals and articles. In order to provide good science education to children, it is important to understand the nature of science, the way contents are organised and presented, the pedagogy adopted, textbooks and other teaching-learning materials, the assessment and evaluation scheme adopted, and so on. All these require an in-depth research to unravel the best practices to be adopted. The present review of research in science education is broadly classified into seven areas, namely—curriculum and teaching-learning resources, cognitive studies, science teaching and learning, creativity, gender issues, achievement in science, and environmental concerns. The essence of researches in each area is given, including the trends and suggestions for further research. The understanding of various issues in science education through these researches will provide insights in improving the science curriculum, teaching-learning materials and pedagogical practices to be followed in teaching science.